Pakistan: On the Way to be Failed State? - Masud, Matiul Hoque; Ahmmed, Helal Uddin; Choudhury, Anwar Hossain; Mostafa, Muhammad Ridwan (Mediterranean Journal of Social Sciences, 2013)
Vibrant political situation and unstable foreign policy has raised the question â€“whether Pakistan a â€œfailed stateâ€ or not- morestrongly. Its dependence on major powers for security and absence of specific sphere of nationalism has made Pakistan moreexposed. Over the last few years Pakistan is going to be considered a â€œfailed stateâ€ because the indicators of a â€œfailed stateâ€have harmonized with the real impasse of Pakistan. Pakistanâ€™s failure as state would have an international and regionalramification. Pakistan backed â€œwar on terrorismâ€ and â€˜balance in South Asiaâ€™ would be more inconsistent if Pakistan failed.International community always would like to solve crisis related to Pakistan to fix up a â€œmenâ€ not by implementing a â€œsystemâ€.Pakistan was used as spring board by big powers for their own interest. If Pakistan failed it would be the first state which is notâ€˜weakâ€™ but â€˜failedâ€™. The paper will discuss the dubious position of Pakistan as failed state; of course, without denying its internaldynamics and imminent tribulations related to its malfunction. The paper at last will propose some guiding principles to solvethe setback.